PENGGUNAAN MEDIA FLASHCARD UNTUK MENINGKATKAN KEMAMPUAN PENGENALAN HURUF SISWA KELAS I DI SD NEGERI LAMPEUNEURUT ACEH BESAR - Cut Rizka Pratiwi; Intan Safiah; Suci Fitriani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
ABSTRACT This study aimed to improve first-grade students' letter recognition skills through the use of flashcard media at SD Negeri Lampeuneurut, Aceh Besar Regency. The study employed a qualitative approach using Classroom Action Research (CAR), conducted in two cycles consisting of planning, implementation, observation, and reflection. The participants were 29 first-grade students. Data were collected through observation and performance tests and analyzed descriptively. The findings showed that the use of flashcards improved students' letter recognition skills. The average score increased from 78.44% in Cycle I to 80.17% in Cycle II, while classical learning mastery improved from 75.86% to 82.75%. Teacher activity also increased from 93.25 to 100, and student activity improved from 73 (good category) to 93.75 (very good category). These findings indicate that flashcard media effectively enhances students' letter recognition skills and promotes active participation in the learning process.